Integrative Entrepreneurship Learning Design: A Study on Islamic Higher Education Institutions in Indonesia - Fetria Eka Yudiana; Sari Famularsih; Alfin Rosyidha; Binti Muflikah; Ahmad Ulliyadhi Satria Raharja (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to explore entrepreneurship courses' challenges and competency needs at Islamic Higher Education Institutions (IHEI) and develop a compatible learning design for these courses. Method: Using a qualitative approach, data was collected through interviews with entrepreneurship lecturers to identify challenges and department heads to understand supporting policies and curriculum development. Additionally, Semester Learning Plans (RPS) content analysis was conducted to examine course content, competencies, and teaching methods. Results: The findings revealed inconsistencies in the entrepreneurship course designs across IHEI. Most courses focus on providing entrepreneurial insights and shifting students' mindsets, with limited practical experiences like essential product sales. Non-classroom entrepreneurship activities vary significantly depending on the lecturers' initiative and departmental coordination. Some departments did not prioritize these activities due to unclear guidance. Novelty: The novelty of this research lies in its proposed integrative learning design, which emphasizes knowledge internalization, skill-building, and attitude formation. The design includes four stages: mindset-building, business experience, start-up business, and business development, offering a structured approach to enhance entrepreneurial competencies in IHEI.